Respostas

2013-09-01T15:55:43-03:00
AB=  4-(-1)=5   -2-2=-4 0-3=-3
-3AB= 5X-3=-15  -4X-3=12  -3X-3=9  LOGO -3AB= (-15,12,9)

  -3AB                                                                   
(-15,12,9)=AP
(-15,12,9)= P-A
(-15,12,9)= P- (-1,2,3)
P= 
 (-15,12,9) + (-1,2,3)
P= (-16,14,12)

CONFERINDO AP= -3AB

       P             A              AP
(-16,14,12) - (-1,2,3) = (-15,12,9) NOTE QUE ESSE VALOR É O MESMO VALOR DE -3AB, COMPROVANDO A IGUALDADE DOS PONTOS.  DÚVIDAS SÓ ME MANDAR UMA MENSAGEM ;)

9 4 9